แบบจำลองระบบจ่ายน้ำประปาของมหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ (MODELING OF WATER DISTRIBUTION SYSTEM OF SRINAKHARINWIROT UNIVERSITY ONGKHARAK) - สายหยุดทอง ชาญวิทย์ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2012)
มหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ มีโรงงานผลิตน้ำประปาและระบบจ่ายน้ำ (Water distribution system) เพื่อจ่ายน้ำให้คณะและตึกต่างๆ แต่สำหรับระบบจ่ายน้ำนั้นยังขาดข้อมูลที่สำคัญต่อการนำไปวิเคราะห์และการออกแบบทางวิศวกรรมหรือนำไปใช้ในการบริหารจัดการ ในการวิจัยนี้ได้ทำการสร้างแบบจำลองโครงข่ายท่อจ่ายน้ำประปาด้วยคอมพิวเตอร์จากข้อมูลภาคสนามแล้วจึงทำการประมวลด้วยการเปรียบเทียบค่าความดัน พบว่ามีการสูญเสียน้ำเป็นจำนวนมากตลอดความยาวท่อ เนื่องจากค่าความดันจากการจำลองแตกต่างจากที่วัดจริงมาก และการสรุปนี้ยังสอดคล้องกับข้อมูลที่สำรวจได้จากโรงประปาที่จ่ายน้ำถึงวันละประมาณ 3,000 ลบ.ม. แต่ใช้จริงเพียง 1,000 ลบ.ม. ต่อวัน จึงมีน้ำสูญหายตลอดความยาวท่อประมาณ 2,000 ลบ.ม. ซึ่งเป็นปริมาณที่มากกว่าร้อยละ 50 คำสำคัญ: ระบบจ่ายน้ำ การสูญเสียน้ำ โครงข่ายท่อ Srinakharinwirot University Ongkharak has both a water treatment plant and a water distribution system for supplying water to a number of buildings. But for distribution system, important data had been absent for analysis in terms of engineering design or management. In this study, the water distribution system was modeled by computer programming from field data. After the model was simulated, the results in terms of pressure showed that there was a substantial difference to the observed data. This is because of a large number of the leakage in the distribution system that made the recorded pressure lower than those of the simulation. This was also supported by survey data that the plant supplied the water of 3,000 m3/d, while only around 1,000 m3 were sent to the buildings in each day. It indicated that 2,000 m3/d were disappeared during the distribution, ie more than 50% lost. Keywords: Water distribution system, Water leakage, Pipe network